Body Enclosure for Corpse - Lee, Shi Hui (Universiti Malaysia Sarawak (UNIMAS), 2019)
This project is about the development of body bag, which offers a safer and more economical alternative to modern variants. A body bag, also known as a cadaver (dead body) pouch or human remains pouch (HRP). Dead bodies can possibly be contagious through microorganisms or the environment whereby we have to minimize the contact of the workers' exposure to blood, bodily fluids and tissues. The objectives of this research are to come out with a design that is feasible to allow dead body to be viewed without any leakage or contamination. Besides, propose the suitable sizes and proportions of body bags to serve different purposes. The methods used in the collection of data for body bags are through online articles and websites, and interview sesssion with the lead forensic scientist of Sarawak General Hospital. Dr. Norliza stated that the dimensions and sizes of the mockup were in line with the industry standards and the size of the window could be increased. The results may lead to the invention of a body bag, which can fulfill the needs ofprofessionals.